Harmonisasi Antara Hukum Kewarganegaraan Indonesia dan Prinsip-Prinsip Hukum Islam: Harmonization Between Indonesian Citizenship Law and Islamic Legal Principles - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Kana Afanin Ridha; Elin Eka Pratiwi; Febriana Nur Azizah (Litera Academica Publishing, 2025)
This study aims to analyze the harmonization between Indonesian citizenship law and Islamic legal principles. Indonesian citizenship law is governed by Law No. 12 of 2006, which outlines various aspects of citizenship administration, while Islamic legal principles encompass teachings from the Qur'an and Hadith regarding individual responsibilities and rights within a state community. This research employs a qualitative approach with methods including document analysis, interviews, and observations to evaluate the alignment and misalignment between the two legal systems. Findings indicate alignment in principles such as trust and equality of rights, yet highlight discrepancies concerning dual citizenship and certain provisions that diverge from Sharia principles. To address these issues, it is recommended to revise policies, foster dialogue between policymakers and scholars, and enhance legal education and outreach. This study aims to contribute to achieving a harmonious balance between Indonesian citizenship law and Islamic legal principles.